Introducing Wellness (Global Journal of Management and Business Research, 2017)
Bangladesh is a lower middle-income country and situated in Southern Asia It is seventh largest country of the world in population Around 80 million people are considered as work force where 41 are female and 59 are male according to World Bank report 2014 Out of 80 million people 2 2 million people are serving public sector 4 5 million people are serving private jobs and rest of the people are involved in agriculture fisheries entrepreneurship NGO and so on Now question is that are the people engaged in service sector getting enough motivation to work Are they getting enough benefits Is there any counseling system for employee s bad time or control employees emotion If the government and the private company s wants to make productive and stress free employees than they have to answer all of the question mentioned To do so Bangladesh can introduce the Wellness and Employee Assistance Program Again it will be a question- what is EAP Employee Assistance Program is a confidential short term counseling service arranged or offered by the employer for employees with personal problems that affect their work performance What is the advantage and disadvantage of EAP Is there any scope EAP can be implemented in the manufacturing and or service sector in Bangladesh Hope and believe at the end all kinds of employer employees and academicians will get all the answers
Keywords: population; employee; motivation; counseling; benefits; wellness